Biosynthesis and characterization of polyhydroxyalkanoates by next-generation industrial biotechnology using lignocellulosic carbohydrates and VFAs as co-substrates - Qian Chen; Yutian Zhang; Xiaojun Ma; Fen Yin; Yingying Zheng; Dongna Li; Jianing Li (Biomass and Bioenergy, 2026)

Prediction of chemoresistance in ovarian cancer based on deep learning with pathological images - Leyan Niu; Xiang Li; Zhiquan Mao; Fen Fu; Mingjie Wang; Hengbin Zhang; Le Chen; Qing Zhang; Xiaoli Tang; Weiming Lou (Functional & Integrative Genomics, 2026)

A facile and scalable strategy to construct superhydrophilic PET membranes for ultrahigh-flux oil–water separation - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Attapulgite from different origins: A comparative study in thin-film nanocomposite nanofiltration membranes for water treatment - Jie Tang; Hangxuan Li; Zhijiang Sun; Li Chen; Ziqing Tang; Fen Ran (Journal of Environmental Chemical Engineering, 2026)

Rapid screening method of glucocorticoid residues in sample-limited cell-cultured meat - Peiwen Yu; Simeng Li; Chen Zhang; Xiaohui Li; Hongping Wang; Fen Jin (Food Research International, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Shrubification increases spatial heterogeneity in soil C:N:P stoichiometry to considerable depth in grazed alpine meadows - Jie Chen; Qiu-jin Ma; Bin Jia; Fen-Can Li; Han Mao; Shu Gang; Yawen Li; Xiao Ming Mou; Xiao Gang Li (CATENA, 2026)

Prospective life cycle assessment for high-value hydrogen from plastic waste by catalytic microwave processing: from laboratory to industrial scale - Zihao Shi; Zhenzhen Hong; Mengying Chen; Mulan Tu; Chuanping Li; Fen Wei; Xiong Peng; Xiaochuan Chen; Junxiong Wu; Yuming Chen; Qinghua Chen; Wei-Qiang Chen; et al. (Resources, Conservation and Recycling, 2026)

Environmentally responsible synthesis of polymer-nano fused composite membranes with long-term stability for sustainable CO2 separation - Hui Shen Lau; Fan Feng; Qiubo Chen; Xue-Li Cao; Shi-Peng Sun; Wai Fen Yong (Chemical Engineering Journal, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Wholly-Tröger's base with strong rigidity-based polyamide loose nanofiltration membranes with excellent permeance, precise dye/salt selectivity, and durability under strongly acidic conditions - Nian Zhang; Jing-Feng Chen; Chen Peng; Dong Yu; Chen-Jie Wei; Li-Fen Liu (Desalination, 2026)

Characterization of gluten quality of single-locus wheat lines with double null alleles at the Glu-1 locus - Shoufen Dai; Lingling Liang; Xiaorong Deng; Sisi Dong; Na Zhang; Chunmei He; Shiqi Luo; Jihao Chen; Fen Lu; Yapeng Li; Zixuan Fan; Bo Lu; et al. (Cereal Research Communications, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

A scalable consensus docking decision-support pipeline for aquaculture bridging foodomics and affordability - Chen-Hsun Liu; Chiu-Hui Kuo; William Chih-Wei Chang; Chih-Hsuan Fan; Bonien Chen; Li-Lian Liu; Fen-Chen Wu; Pao-Chi Liao; Kuohsun Chiu (Computers and Electronics in Agriculture, 2026)

Microplastics enter strawberry fruit tissues directly through the epidermis - Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Lihui An; Fen Jin (Journal of Hazardous Materials, 2026)

Synergistically enhanced mechanical properties, wave-transparency, and low dielectric properties of cyanate ester resins by furfuryl-based diglycidyl-containing hollow polymer microspheres with nanoconfinement effects - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2026)

Reassessing the efficacy and safety of trimethoprim-sulfamethoxazole for Pneumocystis jirovecii pneumonia: a retrospective study - Yangmin Hu; Wei Hu; Danyang Li; Fen Lan; Wei He; Meng Chen; Difei Yao; Junjun Xu; Yujin Lai; Haibin Dai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Integrated catalytic production and separation of 5-hydroxymethylfurfural from fructose using resin-based solid acid and hyper-cross-linked adsorption resin in aqueous media - Hairong Chen; Xuefang Chen; Haifeng Chen; Tessafa Abrham Ashagrie; Bo Chen; Fen Peng; Hairong Zhang; Zhili Li; Xinde Chen (Journal of Environmental Chemical Engineering, 2026)

ECCAS: An interactive web platform for assessing water-sustainable ecosystem productivity in large-scale dryland restoration - Ning Chen; Fen Gou; Weibin Zhang; Xinyao Xu; Nan Gao; Shuai Li; Bojie Fu; Yihe Lü; Shuai Wang; Jianwu Yan; Wei Liang (Journal of Environmental Management, 2026)

Front-face synchronous fluorescence spectroscopy coupled with PLSR for rapid quantitative analysis of Chinese five-spice powder composition - Fei-Yue Chen; Li-Fen Zhang; Hong-Yan Pan; Xia Huang; Pei Yi; Zhi Jin; Peng-Hui Zhu; Jin Tan (Food Research International, 2026)

Cell type-specific contribution of low-density lipoprotein receptor to atherosclerosis - Wei-Hui Li; Yu-Liang Zhang; Ya-Fen Zhang; Zhenyang Yu; Liang Chen; Hao-Yu Fang; Liang Cheng; Bao-Liang Song; Jie Luo (Science China Life Sciences, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Feminizing effects of environmental estrogens on amphibians and the corresponding assays: A narrative review - Shuang-Yan Luo; Yuan-Yuan Li; Zhong-Yang Chen; Hong-Yuan Wang; Zhan-Fen Qin (Journal of Environmental Sciences, 2026)

Potential re-release of Co2+ by using Ceratophyllum demersum L as bioreactors to construct dual-converted Co9S8&Co2P for lithium-ion batteries - Huanzhong Zeng; Rui Liu; Yuanyou Peng; Jiyi Sun; Junlong Chen; Jinling Li; Jianzhou Niu; Fuliang Zhu; Fen Ran (Chemical Engineering Journal, 2026)

Cycloastragenol reduces inflammation and apoptosis in acute lung injury by inhibiting the NF-κB p65 and Akt pathways - Huixian Cheng; Qixiang Xu; Cuifeng Zhang; Liangbin Cao; Fen Yao; Lihui Chen; Min Guo; Sixu Chen; Jiayin Wang; Xiaodong Wang; Qian Li; Yongquan Chen; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Anti-MRSA and cytotoxic activity of a new diamide compound isolated from Aspergillus sp. H30 - Long-Fen Li; Ying-Ying Hu; Xin-Zhu Wang; Qing-Zhou Meng; Pei-Pei Zhao; Qiao-Ni Chen; Ying Xu; Xue-Kui Xia (Natural Product Research, 2026)

First report of a stem disease caused by Alternaria citri Ellis & Pierce on Nicotiana tabacum L. in Guizhou, China - Yingping Zuo; Zhu Li; Mingzhu Chen; Xiaoli Li; Weidong Wang; Fen Tian; Maofa Yang; Lijuan Peng; Haixia Ding (Crop Protection, 2026)

The bactericidal efficacy of carvacrol against drug-resistant Streptococcus iniae and its protective effects on channel catfish (Ictalurus punctatus) - Lizi Yin; Minmin Wang; Jianing Wu; Xiaonan Li; Fen Chen; Bowen Liu; Yi Geng; Xiaoli Huang; Defang Chen; Ping Ouyang (Aquaculture, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Schizophyllum commune polysaccharide ameliorates diet-induced obesity by regulating the Faecalibaculum rodentium/indole-3-lactic acid/microRNA axis - Chaomin Yin; Chen Li; Xiuzhi Fan; Defang Shi; Jiangtao Li; Jianhui Qiu; Fen Yao; Wei Yu; Hong Gao (Carbohydrate Polymers, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

Gene expressions in newborns and the association with prenatal exposure to phthalate plasticizers – The Taiwan Maternal and Infant Cohort Study (TMICS) - Yi-Ju Wu; Hui-Ju Wen; Chung-Hsing Chen; Shin-Fen Tsai; Shih Sheng Jiang; Shu-Li Wang (Journal of Hazardous Materials, 2025)

Palmitoylation modulates antitumor immunity - Feng Tang; Jia-Long Xu; Qing Zhang; Xi Chen; Ze-Fen Wang; Ya-Di Xu; Zhi-Qiang Li (Molecular Biology Reports, 2025)

Curcumin suppresses NLRP3 inflammasome activation by inducing autophagy to alleviate neuropathic pain in rats - Tiantian Zhou; Ziyang Chen; Sha Li; Fen Wang; Weiqian Tian (Molecular Biology Reports, 2025)

Association between legume consumption and risk of esophageal cancer among Chinese adults: a 17-year prospective cohort study - Fengyi Huang; Xiaorui Zhang; Jiayue Li; Xinqing Li; Ru Chen; Shaoming Wang; Fen Liu; Wenqiang Wei (Cancer Causes & Control, 2025)

The role of arachidonic acid metabolites in major depressive disorder: mechanisms and therapeutic implications - Yanjie Qin; Jiaxin Li; Fen Chen; Liu Wang; Bo Tao; Xuejia Zhai; Yongning Lu (Metabolic Brain Disease, 2025)

Multi-parameter analysis and safety assessment of thermal runaway triggered by side heating of batteries with different cathode materials - Bowei Chen; Jianfeng Wang; Yuhan Li; Fen Liu; Zhen Liu; Zhiwen Zuo; Yongkai Jia; Chunyan Wang; Yanyan Wang (Process Safety and Environmental Protection, 2025)

Production of nickel matte from saprolitic laterite ore by sulfide smelting with pyrite - Wei Liu; Shiyang Liu; Hongbin Ling; Chen Li; Fen Jiao (Minerals Engineering, 2025)

A novel high selectivity, strong acid resistance and antifouling polyamide thin film composite nanofiltration membrane fabricated with 3,3′-diamine-Tröger's base - Liu-Yang Gong; Nian Zhang; Jun-Yan Yu; Yan-Nan Wu; Chen-Jie Wei; He-Lin Zhu; Xue-Li Cao; Li-Fen Liu (Desalination, 2025)

Two pairs of isomeric resin glycosides from Argyreia obtusifolia - Shuo Chen; Yi-Lin Niu; Zhi-Tong Li; Hong-Hua Cui; Yong-Qin Yin; Yan-Fen Chen (Phytochemistry Letters, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Dynamic pore engineering in COF-based nanozymes: Construction of hydrogen-bond-mediated confinement catalysis for enhanced asymmetric aldol reactions - Shizhao Wang; Qi Chen; Jiankang Li; Danni Lin; Ka Li; Chuangxin Dong; Xiao Xiao; Fen-Er Chen (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Responses of anuran diversity and community structure to an urbanization gradient in a subtropical Asian city - Yung-Chih Lai; Cheng-En Li; Wei-Chun Cheng; Tien-Chen Lai; Pei-Fen Lee; Yi-Ju Yang (Urban Ecosystems, 2025)

The role of N6-methyladenosine (m6A) modification in plants - Cui-Xian Qin; Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Miao Wang; You-Qiang Pan; Li Zhou; Bao-Qing Zhang; Jian-Hui Zhou; Dong-Liang Huang (Theoretical and Applied Genetics, 2025)

Carbon and nitrogen footprints of rice in China: implications for low-carbon rice consumption - Jingyu Zhang; Yingchun Li; Shifeng Li; Fen Ma; Guojun Cao; Guohui Chen; Yanfang Chen; Chunfeng Peng (Nutrient Cycling in Agroecosystems, 2025)

Arsenite antiporters ACR3/3;1 are critical for Se-enhanced plant growth and As accumulation in As-hyperaccumulators Pteris multifida and Pteris cretica - Wei Li; Si-Xue He; Yi-Wen Liu; Qian-Yu Zhou; Shu-Fen Xiao; Yanshan Chen; Yue Cao; Lena Q. Ma (Journal of Hazardous Materials, 2025)

Novel furfuryl-based phosphaphenanthrene containing N/P flame retardant: towards epoxy resin with excellent flame retardancy, enhanced toughness and low dielectric constant - Quanbing Shen; Beibei Yu; Dong Chen; Fen Zhang; Li Wang; Yuhong Ma; Wantai Yang (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Karyotype and evolution trend analysis of seven diploid accessions and their autotetraploid lines of Tartary buckwheat native to China - Li-kun Lian; Pei Zhang; Xiao-fen Wu; Yi-zhong Zhang; Qing-fu Chen (Genetic Resources and Crop Evolution, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Bellidifolin, a constituent from edible Mongolic Liver Tea (Swertia diluta), promotes lipid metabolism by regulating intestinal microbiota and bile acid metabolism in mice during high fat diet-induced obesity - Aikebaier Jumai; Shaohua Chen; Yaodan Wu; Fen Liu; Bailin Li; Baojun Zhu; Liyun Zhao; Kanglun Liu; Qingzhong Zhang; Sheng-Xiang Qiu (Food Bioscience, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

Discovery of phenoxazine congeners as novel α-glucosidase inhibitors and identification of their biosynthetic gene cluster from Streptomyces sp. CB00316 - Lin Jiang; Pingzhi Huang; Aijie Li; Bin Fen; Yani Zhong; Caijun Tang; Guangling Wu; Wenlei Wang; Yuhan Chen; Jian Pan; Genyun Tang; Hong Pu (Archives of Microbiology, 2025)

Organic matter burial and degradation in the southern South China Sea since the last glaciation - Fen Chen; Shengyi Mao; Wanqiu Zhou; Gang Li; Xiaowei Zhu; Wen Yan (Global and Planetary Change, 2025)

Shrubs increase phosphorus transformation from inorganic to organic form via lowering soil pH in grazed alpine meadows - Jie Chen; Yawen Li; Bin Jia; Fen-Can Li; Xiao Ming Mou; Shu Gang; Xiao Gang Li (Agriculture, Ecosystems & Environment, 2025)

Evaluation of the antibacterial activity and mechanism of cannabigerol against drug-resistant Streptococcus iniae in vitro - Jianing Wu; Minmin Wang; Tingke He; Xiaonan Li; Bowen Liu; Fen Chen; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Ping Ouyang (Archives of Microbiology, 2025)

Dissipation patterns of trisiloxane ethoxylates in cucumber plants and field soils: Insights from different end-capping groups - Simeng Li; Xiaohui Li; Chen Zhang; Bowen Li; Peiwen Yu; Qin Dai; Hongping Wang; Fen Jin (Journal of Hazardous Materials, 2025)

Application of microfluidics for revealing physiological metabolic response of algae at the single-cell level - Yu-Fen Qiao; Song-Ya Li; Ting-Ting Liu; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Journal of Environmental Chemical Engineering, 2025)

Dynamic proteome and acetylome profiling reveals key regulators of sucrose accumulation in sugarcane - Miao Wang; Ao-Mei Li; Zhong-Liang Chen; Cui-Xian Qin; Fen Liao; You-Qiang Pan; Prakash Lakshmanan; Xiao-Feng Li; Dong-Liang Huang (Plant Cell Reports, 2025)

Humidity controls soil organic carbon accrual in grassland on the Qinghai–Tibet Plateau - Zhen-Huan Guan; Bin Jia; Zi-qi Niu; Xiao-Ming Mou; Jie Chen; Fen-Can Li; Yi-Ning Wu; Shijie Ning; Kuzyakov Yakov; Xiao Gang Li (Soil Biology and Biochemistry, 2025)

The regulatory mechanism controlling nitrification inhibitors-induced mitigation of nitrification and NO3−-N leaching in alkaline purple soil - Fabo Liu; Prakash Lakshmanan; Wenxin Zou; Ming Lang; Zhao Lei Li; Fen Zhang; Tao Liang; Jing Chen; Yan Wang; Xiaozhong Wang; Xinping Chen (Journal of Environmental Management, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Large-scale ecological infrastructures enhance the productivity of agro-socio-ecological systems by reducing soil erosion in the Loess Plateau - Fen Gou; Wei Liang; Yan Liu; Bojie Fu; Zhenguo Wang; Weibin Zhang; Zhigang Chen; Jianwu Yan; Junyi Li; Yihe Lv (Journal of Environmental Management, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Efficiency and mechanism of sludge thickening by a novel sandwich-like forward osmosis composite membrane constructed on microporous polyethylene separator - Fen Chen; Jingyuan Yu; Jintai Hu; Guoqing Zhang; Chunhui Du; Xuchun Li (Chemical Engineering Journal, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Distribution, bioaccumulation and human exposure risk of bisphenol analogues, bisphenol A diglycidyl ether and its derivatives in the Dongjiang River basin, south China - Danlin Yang; Daoming Zhao; Honglin Chen; Yanpeng Cai; Yuxian Liu; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue; Kurunthachalam Kannan (Science of The Total Environment, 2024)

Intensifying the selective sulfidation of nickel in saprolitic laterites by sodium salts - Chen Li; Wei Liu; Fen Jiao; Tianfu Zhang; Junwei Han; Wenqing Qin (Minerals Engineering, 2024)

3D in-situ stress prediction for shale reservoirs based on the CapsNet-BiLSTM hybrid model - Fen Lyu; Junping Liu; Li Chen; Bocheng Tao; Xingye Liu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Fabrication of thermo-responsive microcapsule pesticide delivery system from maleic anhydride-functionalized cellulose nanocrystals-stabilized pickering emulsion template - Jun Li; Chao Wu; Hong-jun Xu; Jia-wei Ding; Yong-jiang Li; Hui Jiang; Hui-fen Su; Sheng Chen; Xin Li; Muhammad Asif Javaid; De-qiang Li (Carbohydrate Polymers, 2024)

Two-way coupling fluid–structure interaction analysis on dynamic response of offshore wind turbine - Fen Li; Jiaojiao Fu; Jiahui Chen; Dan Hu (Marine Georesources & Geotechnology, 2024)

Two ethylene-responsive transcription factors, AdVAL2 and AdKAN2, regulate early steps in kiwifruit starch degradation - Yang Tong; Wen-yue Su; Yu-tong Chen; Xiao-fen Liu; Qiu-yun Zhang; Tong-hui Qi; Andrew C. Allan; Xiang Li; Xue-ren Yin (Postharvest Biology and Technology, 2024)

A comparison of the physicochemical properties, allergenicity, and stability of recombinant β-lactoglobulin: Development of standard bovine milk allergens - Fen Xie; Wei Hu; Xuanyi Meng; Chunqiu Hu; Xin Li; Hongbing Chen (Food Bioscience, 2024)

The Ecological Niches and Interspecific Associations of the Dominant Fishes in the Xiamen Seas, China - Liang-Min Huang; Hao-Qi Xu; Jia-Yue Yu; Yong-He Chen; Jia-Qiao Wang; Fen-Fen Ji; Jun Li; Jian-Di Cai; Ta-Jen Chu (Fishes, 2024)
Fish are vital in enhancing the stability of marine ecosystems. Therefore, understanding the ecological niches and interspecific correlation characteristics of their dominant species provides a good scientific basis for the protection and management of marine biodiversity. In this study, on the basis of survey data from trawls conducted in the waters off Xiamen in the spring (April) and autumn (November) of 2021, the ecotopes and interspecies connectivity of the dominant fish species were investigated using the relative importance index (IRI), χ2 tests, the association coefficient (AC), and Pearson and Spearman analyses. According to the IRI, there were 23 fish species with higher values, including 15 species in spring and 15 species in autumn. The 15 dominant fish species could be subdivided into wide-, medium-, and narrow-ecotope species, of which there were 2 and 3 wide-ecotope types in spring and autumn. The niche overlap indices exhibited a range of 0.000–0.809 in the spring and 0.000–0.915 in the autumn, showing small differences between the two seasons. The interspecific correlations between the dominant fishes in Xiamen’s waters in spring and autumn were weak, and both showed non-significant positive correlations, indicating that the correlations between the dominant fishes in this sea area are relatively independent. The findings of this investigation provide a fundamental database and theoretical framework for researching the adaptive mechanisms of marine fish in the Xiamen Seas.

Selenium alleviates chromium stress and promotes chromium uptake in As-hyperaccumulator Pteris vittata: Cr reduction and cellar distribution - Qian-Yu Zhou; Wei Li; Si-Xue He; Song-Ge Deng; Shu-Fen Xiao; Chen-Jing Liu; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Foliar-selenium enhances plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Critical roles of GSH-GSSG cycle and arsenite antiporters PvACR3 - Wei Li; Si-Xue He; Qian-Yu Zhou; Zhi-Hua Dai; Chen-Jing Liu; Shu-Fen Xiao; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Silk-fibroin-based nanofibrous scaffolds integrated with nano-engineered living bacteria enabling antibiotic-free accelerated infected wound healing - Ming Teng; Xiaomin Luo; Fen Ao; Liuying Li; Jianyan Feng; Peng Zhang; Xiaomeng Zhang; Xudan Liu; Chen Yang; Lufeng Ji; Xuechuan Wang; Haiyan Ju; et al. (Chemical Engineering Journal, 2024)

Superwetting MAX@SiO2 coatings with high photothermal conversion performances for efficient seawater desalination and anti-/de-icing - Helong Zhang; Chuxiong Qiu; Rong Zhang; Hao Zhang; Yunxia Chen; Tao Zeng; Fen Qiao; Lee Li; Ghafar Ali; Xiujian Zhao; Yi Xie (Chemical Engineering Journal, 2024)

Ucf-101 alleviates Ischaemia/Reperfusion induced retinal inflammation and injury via suppressing oxidative damage - Yuan-Jun Qin; Guangyi Huang; Jing Liao; Li Jiang; Fen Tang; Ningning Tang; Yiyi Hong; Chaolan Shen; Qianqian Lan; Fan Xu; Lifei Chen (Journal of Molecular Histology, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Dissipation and potential risk of tristyrylphenol ethoxylate homologs in peanuts by spraying and root irrigation: A comparative assessment - Hongping Wang; Minjie Li; Simeng Li; Xueying Chen; Bowen Li; Hua Shao; Fen Jin (Journal of Hazardous Materials, 2024)

Amplifying enantioselectivity in asymmetric transformations using heterogeneous chiral single-rhodium-site catalyst with sustained catalytic activity - Junwen Wang; Feng Liang; Junrong Huang; Jun Li; Jingyuan Liao; Chengyao Zhao; Hengzhi You; Tao Tu; Fen-Er Chen (Chemical Engineering Journal, 2024)

Liquiritin inhibits TGF-β1-induced epithelial mesenchymal transition and extracellular matrix deposition in human renal proximal tubular epithelial cells by suppressing the MAPK signaling - Zhen Chen; Yi jue Liu; Bo Yu; Wei Li; Mengli Zhang; Xian Wu; Feng Gui; Huan Peng; Fen Ai (Molecular & Cellular Toxicology, 2024)

Individual and combined treatments of 2,4-epibrassinolide (EBR) and calcium chloride (CaCl2) maintain the postharvest quality of baby mustard - Hongmei Di; Ruobin Liu; Yutong Zhang; Zhifeng Chen; Jie Ma; Victor Hugo Escalona; Duchen Liu; Huanhuan Huang; Zhi Huang; Yi Tang; Huanxiu Li; Bo Sun; et al. (Postharvest Biology and Technology, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Refined building thermal climate zoning scheme in regions with mountainous terrain for accurate building energy-saving potential estimation - Tianyu Zhang; Mingcai Li; Yong Wang; Jie Zhou; Yonghua Li; Fen Zhang; Jingfu Cao; Xianyan Chen; Bao-Jie He (Energy and Buildings, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Effects of dietary astaxanthin on growth performance, immunity, and tissue composition in largemouth bass, Micropterus salmoides - Jiankun Zhang; Yeshun Yang; Hanying Xu; Xinyu Li; Fen Dong; Qiang Chen; Tao Han; Jiteng Wang; Chenglong Wu (Frontiers in Marine Science, 2024)
This study examined the effects of feeding largemouth bass ( Micropterus salmoides ) with diets containing different doses of astaxanthin (0, 50, 100, 150, and 200 mg/kg) for 8 weeks. The results showed that the values of weight gain significantly increased from 620.32 ± 50.38% to 826.14 ± 33.49% as dietary astaxanthin levels increased from 0 mg/kg to 100 mg/kg. When the astaxanthin level exceeded 150mg/kg, the weight gain rate showed a downward trend, but there was no significant difference among of the 100, 150 and 200 mg/kg groups. The feed conversion ratio (FCR) and protein efficiency ratio (PER) were also improved by adding astaxanthin to diets ( P < 0.05). Meanwhile, adding astaxanthin to the feed increased the length and thickness of intestinal villus and muscle layer thickness ( P < 0.05). The astaxanthin supplementation increased the expression of the NF-E2-related factor ( Nrf2 ) gene and reduced malondialdehyde (MDA) content and the expression of apoptosis genes Caspase-9 and Caspase-3 ( P < 0.05), indicating that it has a good antioxidant ability. Furthermore, adding astaxanthin increased the content of non-specific immune markers and decreased the expression levels of the inflammatory factors interleukin-15 ( IL-15 ) and tumor necrosis factor-α ( TNF-α ). Moreover, fish fed diets with astaxanthin exhibited lower blood cortisol levels ( P < 0.05). The proportions of C20:4n6 (ARA) and C20:5n3 (EPA) in the liver decreased with increasing dietary astaxanthin levels. Based on WGR and SGR values, the optimal addition level of astaxanthin in largemouth bass feed is 134.8 mg/kg ~ 135.75 mg/kg. In summary, the appropriate dietary astaxanthin enhanced the antioxidant capacity and immune response of largemouth bass and had a positive effect on its intestinal health.

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Regulation of soil nitrogen cycling by shrubs in grasslands - Jie Chen; Fen-Can Li; Bin Jia; Shu Gang; Yawen Li; Xiao Ming Mou; Yakov Kuzyakov; Xiao Gang Li (Soil Biology and Biochemistry, 2024)

Large-scale quantum emulating simulations of biomolecules: A pilot exploration of parallel quantum computing - Honghui Shang; Fei Wang; Yi Fan; Huan Ma; Qi Liu; Chu Guo; Pengyu Zhou; Qi Chen; Qian Xiao; Tianyu Zheng; Bin Li; Fen Zuo; et al. (Science Bulletin, 2024)

Cotton crop transpiration reveals opportunities to reduce yield loss when applying defoliants for efficient mechanical harvesting - Yongfan Chen; Jochem B. Evers; Mingfeng Yang; Xuejiao Wang; Zeshan Zhang; Shuai Sun; Yutong Zhang; Sen Wang; Fen Ji; Dao Xiang; Jie Li; Chunrong Ji; et al. (Field Crops Research, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Determination of the Elemental Iodine in Human Breast Milk by Inductively Coupled Plasma mass Spectrometry - Chun-Jui Huang; Jia-Zhen Li; Chii-Min Hwu; Harn-Shen Chen; Chang-Ching Yeh; Fan-Fen Wang; Chen-Chang Yang (Biological Trace Element Research, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Anthropogenic multipollutant input to the offshore South China Sea - Fen Chen; Shengyi Mao; Gang Li; Yuhang Tian; Li Miao; Weihai Xu; Xiaowei Zhu; Wen Yan (Science of The Total Environment, 2024)

Imidacloprid triggered changes in strawberry fruits on edible quality and phenolic profiles by applied at two growth stages - Ning Yue; Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Xueying Chen; Fen Jin (Food Research International, 2024)

The brominated flame retardant tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) as well as hexabromocyclododecane lead to lipid disorders in mice - Xuan-Yue Chen; Yuan-Yuan Li; Lin Lv; Yi-Ming Xiong; Zhan-Fen Qin (Environmental Pollution, 2024)

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

Eigenfunction expansion solution for wave diffraction from a uniform cylinder in front of a partially reflective wall - Bin Teng; Gao-fei Su; Ying Gou; Li-fen Chen (Ocean Engineering, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

An artificial multienzyme cascade for the whole-cell synthesis of rare ketoses from glycerol - Yahui Gao; Fen Li; Yulu Wang; Zhou Chen; Zijie Li (Biotechnology Letters, 2023)

Analysis of Sharp Eagle Oscillating Surge Wave Energy Converter Based on a Two-Dimensional Numerical Wave Flume Model - Liang Sun; Zewang Yang; Mingsheng Chen; Fen Li (Journal of Marine Science and Engineering, 2023)
To investigate the overtopping and slamming phenomena that occur in the interactions between waves and oscillating surge wave energy converters (OSWECs), a two-dimensional numerical wave flume was established using computational fluid dynamics (CFD) software Fluent by adding the momentum source terms into the original Navier–Stokes equation. Numerical convergence studies of the mesh sizes and time steps were firstly performed to ensure the sufficient accuracy of the numerical model. The variations in the wave heights along the wave propagation direction in the wave-generating area, working area, and wave-absorbing area were analyzed. The dynamics of the flap-type OSWEC were simulated using the overset mesh function embedded in Fluent. In addition, the numerical results were compared with the experimental data, and good agreements were achieved. External torque was applied to the hinge joint of the OSWEC to simulate the forces due to the power take-off (PTO) system, and the identified optimal PTO damping was compared with the numerical results based on the potential flow theory, which verified the correctness of the numerical PTO system. On this basis, nonlinear wave slamming by the sharp-eagle OSWEC was analyzed. The results show that under certain incident wave conditions, the sharp-eagle OSWEC can effectively reduce the maximum rotation angle and angular velocity compared with those of the flap-type OSWEC, and there is no overtopping that occurring for the sharp-eagle OSWEC. Furthermore, the sharp-eagle OSWEC performs better than the flap-type OSWEC.

pH-Regulated lignin as a green catalyst for Highly-Efficient CO2 cycloaddition - Yidan Ouyang; Bin Lei; Zhouqing Tan; Fen Hu; Zhao Wu; Jiaxue Wang; Yixuan Ma; Ran Zhang; Li Guo; Feifei Chen (Fuel, 2023)

Hexavalent chromate bioreduction by a magnetotactic bacterium Magnetospirillum gryphiswaldense MSR-1 and the effect of magnetosome synthesis. - Siang Chen Wu; Wei-Che Hsiao; Ya-Chun Zhao; Li-Fen Wu (Chemosphere, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Metagenomic evidence for antibiotics-driven co-evolution of microbial community, resistome and mobilome in hospital sewage - Jiayu Sun; Yumeng Yuan; Leshan Cai; Mi Zeng; Xin Li; Fen Yao; Weidong Chen; Yuanchun Huang; Muhammad Shafiq; Qingdong Xie; Qiaoxin Zhang; Naikei Wong; et al. (Environmental Pollution, 2023)

Temporal decline of genetic differentiation among populations of western flower thrips across an invaded range - Li-Na Sun; Li-Jun Cao; Jin-Cui Chen; Li-Jun Ma; Gui-Fen Zhang; San-An Wu; Ary Anthony Hoffmann; Shu-Jun Wei (Biological Invasions, 2023)

Potential translocation process and effects of polystyrene microplastics on strawberry seedlings - Chen Zhang; Ning Yue; Xiaohui Li; Hua Shao; Jing Wang; Lihui An; Fen Jin (Journal of Hazardous Materials, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Ancient hydrocarbon slicks recorded by a coral atoll in the South China Sea - Xiaowei Zhu; Guodong Jia; Yuhang Tian; Fen Chen; Gang Li; Weihai Xu; Li Miao; Wen Yan (Chemical Geology, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Corolliform morphology thin film composite polyamide membrane constructed via Tröger's base PIM for enhancing nanofiltration separation performances - Tian-Hui Chen; Ting Su; Li Xia; Liu-Yang Gong; Bei-Na Dong; Li-Fen Liu (Desalination, 2023)

Urinary cadmium and peripheral blood telomere length predict the risk of renal function impairment: a study of 547 community residents of Shanxi, China - Jia-Chen Zhang; Shuang-Jing Li; Jian-Yong Guo; Guo-Yan Zhang; Hui Kang; Xiu-Jing Shi; Han Zhou; Yu-Fen Liang; Wei-Tong Shen; Li-Jian Lei (Environmental Science and Pollution Research, 2022)

Decoupling of soil organic carbon and nutrient mineralization across plant communities as affected by microbial stoichiometry - Jie Chen; Bin Jia; Shu Gang; Yawen Li; Fen-Can Li; Xiao Ming Mou; Yakov Kuzyakov; Xiao Gang Li (Biology and Fertility of Soils, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Migration of mineral oil hydrocarbons from food contact papers into food simulants and extraction from their raw materials - Jing Jing Pan; Yan Fen Chen; Jian Guo Zheng; Changying Hu; Dan Li; Huai Ning Zhong (Food Additives & Contaminants: Part A, 2021)

Investigation on lateral bearing capacity of monopile under combined vertical-lateral loads and scouring condition - Fen Li; Peisan Tian; Lixian Wang; Mingsheng Chen (Marine Georesources & Geotechnology, 2021)

Effects of habitat fragmentation on the demography of the critically endangered tree Pterospermum kingtungense (Sterculiaceae) in Yunnan, China - Chun-Ming Yuan; Shan-Shan Zhang; Guo-Ping Yang; Jian Chen; Yun-Fen Geng; Xiao-Shuang Li; Wen-Zhong Yang (Tropical Ecology, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Interleukin-1β in hypothalamic paraventricular nucleus mediates excitatory renal reflex - Fen Zheng; Chao Ye; Guo-Wei Wan; Bing Zhou; Ying Tong; Jian-Zhen Lei; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Neuronal Activity in the Cerebellum During the Sleep-Wakefulness Transition in Mice - Li-Bin Zhang; Jie Zhang; Meng-Jia Sun; Hao Chen; Jie Yan; Fen-Lan Luo; Zhong-Xiang Yao; Ya-Min Wu; Bo Hu (Neuroscience Bulletin, 2020)

MESP2 variants contribute to conotruncal heart defects by inhibiting cardiac neural crest cell proliferation - Erge Zhang; Jianping Yang; Yang Liu; Nanchao Hong; Huilin Xie; Qihua Fu; Fen Li; Sun Chen; Yu Yu; Kun Sun (Journal of Molecular Medicine, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Angiotensin Type 1 Receptors and Superoxide Anion Production in Hypothalamic Paraventricular Nucleus Contribute to Capsaicin-Induced Excitatory Renal Reflex and Sympathetic Activation - Yun Qiu; Fen Zheng; Chao Ye; Ai-Dong Chen; Jue-Jin Wang; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Neuroscience Bulletin, 2020)

Analysis of an improved workflow of endoscope reprocessing for bedside endoscopic diagnosis and treatment on COVID-19 patients - Qing Gu; Hua-fen Wang; Ying Fang; Ye Lu; Zhe Shen; Yan Wang; Xin Wu; Li Cen; Yi-shu Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Synthesis, Formulation, and Characterization of Doxorubicin-Loaded Laponite/Oligomeric Hyaluronic Acid-Aminophenylboronic Acid Nanohybrids and Cytological Evaluation against MCF-7 Breast Cancer Cells - Yue Yang; Jinyu Li; Fen Chen; Sen Qiao; Yunjian Li; Weisan Pan (AAPS PharmSciTech, 2020)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Analog simulation of urban construction land supply and demand in Chang-Zhu-Tan Urban Agglomeration based on land intensive use - Ying Xiong; Yun Chen; Fen Peng; Jingzhi Li; Xiaojing Yan (Journal of Geographical Sciences, 2019)

Anti-secretogranin III therapy of oxygen-induced retinopathy with optimal safety - Fen Tang; Michelle E. LeBlanc; Weiwen Wang; Dan Liang; Ping Chen; Tsung-Han Chou; Hong Tian; Wei Li (Angiogenesis, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Downscaling satellite‐derived daily precipitation products with an integrated framework - Fengrui Chen; Yongqi Gao; Yiguo Wang; Fen Qin; Xi Li (International Journal of Climatology, 2019)
Spatially downscaling satellite precipitation products have been performed on annual and monthly precipitation. Accurate downscaling on daily precipitation remains a challenge due to the limitation of the downscaling assumption, the large spatial discontinuity of daily precipitation, and the relatively poor quality of satellite‐derived daily precipitation product. In this study, an integrated downscaling‐fusion framework was proposed and used to downscale satellite‐derived daily precipitation. First, a spatio‐temporal downscaling scheme is applied to produce preliminary downscaled daily precipitation. The accuracy of the derived preliminary results is then boosted by merging with daily gauge observations using an ensemble fusion method. The performance of the proposed framework was tested and evaluated by downscaling the Integrated Multi‐satellite Retrievals for Global Precipitation Measurement (IMERG) daily precipitation data from 0.1 to 0.01° over eastern and central China for the period of 2015–2016. The results showed that (a) the downscaling scheme accurately mapped the spatio‐temporal variation in daily precipitation, and the preliminary downscaled results perfectly maintained the accuracy of the original IMERG data; (b) the fused results were much more accurate than the original IMERG data, decreasing the root‐mean‐square errors (RMSEs) by 22, 10, and 18% at daily, monthly, and annual timescales, respectively, for the whole period; and (c) the fused daily precipitation data considerably strengthened the detection of rain/no rain area compared with the original IMERG daily precipitation data, with a 17% reduction in the inconsistency index.

Structure-Based Gastro-Retentive and Controlled-Release Drug Delivery with Novel 3D Printing - Haoyang Wen; Bosai He; Haoyu Wang; Fen Chen; Pingfei Li; Mengsuo Cui; Qijun Li; Weisan Pan; Xinggang Yang (AAPS PharmSciTech, 2019)

Nucleocapsid protein from porcine epidemic diarrhea virus isolates can antagonize interferon-λ production by blocking the nuclear factor-κB nuclear translocation - Ying Shan; Zi-qi Liu; Guo-wei Li; Cong Chen; Hao Luo; Ya-jie Liu; Xun-hui Zhuo; Xing-fen Shi; Wei-huan Fang; Xiao-liang Li (Journal of Zhejiang University-SCIENCE B, 2018)

Identification of ZFPM2 mutations in sporadic conotruncal heart defect patients - Tian Pu; Yang Liu; Rang Xu; Fen Li; Sun Chen; Kun Sun (Molecular Genetics and Genomics, 2018)

Minimally Toxic Dose of Lipopolysaccharide and α-Synuclein Oligomer Elicit Synergistic Dopaminergic Neurodegeneration: Role and Mechanism of Microglial NOX2 Activation - Wei Zhang; Jun-hua Gao; Zhao-fen Yan; Xi-yan Huang; Peng Guo; Li Sun; Zhuo Liu; Yang Hu; Li-jun Zuo; Shu-yang Yu; Chen-Jie Cao; Xiao-min Wang; et al. (Molecular Neurobiology, 2018)

Abietane diterpenoids from Cephalotaxus lanceolata - Xiao-Jiao Chen; Ling Ni; Mei-Fen Bao; Li Wang; Xiang-Hai Cai (Natural Product Research, 2017)

Modern greenhouse culture of juvenile soft-shelled turtle, Pelodiscus sinensis - Jing Zhang; Fen Wang; Ye-Lin Jiang; Guan-Jun Hou; Yun-Sheng Cheng; Hong-Lian Chen; Xiang Li (Aquaculture International, 2017)

Strain distribution, growth eccentricity, and tension wood distribution in the plagiotropic and orthotropic branches of Koelreuteria henryi Dummer - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

Polymorphisms of the FT gene as a tool to identify underground rhizome types of bamboos - Zai-en Xu; Hong-jun Chen; Li-fen Ji; Ming-bing Zhou; Xiao-qin Guo (Euphytica, 2017)

Sublethal and transgenerational effects of sulfoxaflor on the biological traits of the cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae) - Xuewei Chen; Kangsheng Ma; Fen Li; Pingzhuo Liang; Ying Liu; Tianfeng Guo; Dunlun Song; Nicolas Desneux; Xiwu Gao (Ecotoxicology, 2016)

Egr-1 deficiency protects from renal inflammation and fibrosis - Li-Chun Ho; Junne-Ming Sung; Yi-Ting Shen; Huei-Fen Jheng; Shun-Hua Chen; Pei-Jane Tsai; Yau-Sheng Tsai (Journal of Molecular Medicine, 2016)

Study of tension wood in the artificially inclined seedlings of Koelreuteria henryi Dummer and its biomechanical function of negative gravitropism - Li-Fen Hung; Ching-Chu Tsai; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2016)

A monitoring indicator system for remote sensing of grassland vegetation growth and suitability evaluation – a case study of the Xilingol Grassland in Inner Mongolia, China - Xiuchun Yang; Bin Xu; Xiaohua Zhu; Yunxiang Jin; Jinya Li; Fen Zhao; Shi Chen; Jian Guo; Hailong Ma; Haida Yu (International Journal of Remote Sensing, 2015)

Characterizing changes in grassland desertification based on Landsat images of the Ongniud and Naiman Banners, Inner Mongolia - Jinya Li; Bin Xu; Xiuchun Yang; Yunxiang Jin; Lina Zhao; Fen Zhao; Shi Chen; Jian Guo; Zhihao Qin; Hailong Ma (International Journal of Remote Sensing, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Effect of Trash Addition to the Soil on Microbial Communities and Physico-Chemical Properties of Soils and Growth of Sugarcane Plants - Qing Liao; Guang-Po Wei; Gui-Fen Chen; Bin Liu; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2014)

Hyaluronan-Based Nanocarriers with CD44-Overexpressed Cancer Cell Targeting - Shuangshuang Song; Huan Qi; Jingwen Xu; Pan Guo; Fen Chen; Fei Li; Xinggang Yang; Naicheng Sheng; Yingliang Wu; Weisan Pan (Pharmaceutical Research, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

New species and new records of Rhytismataceae from Japan - Zhi-Jie Li; Ning Cao; Hui-Fen Chen; J. E. Taylor; Cheng-Lin Hou (Mycological Progress, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

Uncertainty analysis of downscaling methods in assessing the influence of climate change on hydrology - Fen Ouyang; Haishen Lü; Yonghua Zhu; Jianyun Zhang; Zhongbo Yu; Xi Chen; Min Li (Stochastic Environmental Research and Risk Assessment, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Multifunctional Tumor-Targeting Nanocarriers Based on Hyaluronic Acid-Mediated and pH-Sensitive Properties for Efficient Delivery of Docetaxel - Shuangshuang Song; Fen Chen; Huan Qi; Fei Li; Tiegang Xin; Jingwen Xu; Tiantian Ye; Naicheng Sheng; Xinggang Yang; Weisan Pan (Pharmaceutical Research, 2014)

In vitro study of nano-HA/PLLA composite scaffold for rabbit BMSC differentiation under TGF-β1 induction - Weimin Zhu; Kang Chen; Wei Lu; Qifeng Sun; Liangquan Peng; Wenzhe Fen; Hao Li; Yangkan Ou; Haifeng Liu; Daping Wang; Yanjun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2014)

Kocuria rosea HN01, a newly alkaliphilic humus-reducing bacterium isolated from cassava dreg compost - Chun-Yuan Wu; Nan Chen; Hong Li; Qin-Fen Li (Journal of Soils and Sediments, 2014)

LXRα gene expression, genetic variation and association analysis between novel SNPs and growth traits in Chinese native cattle - Yun Ma; Ningbo Chen; Rongrong Li; Yongjie Xu; Fen Li; Junya Li; Shuxin Gao; Xiaofeng Li; Kuilin Shi (Journal of Applied Genetics, 2014)

Is there a difference in cognitive development between preschool singletons and twins born after intracytoplasmic sperm injection or in vitro fertilization? - Lan-Feng Xing; Yu-Li Qian; Lu-Ting Chen; Fan-Hong Zhang; Xin-Fen Xu; Fan Qu; Yi-Min Zhu (Journal of Zhejiang University-SCIENCE B, 2014)

Improvement of fluorescent chromosome in situ PCR and its application in the phylogeny of the genus Fagopyrum Mill. using nuclear genes of chloroplast origin (cpDNA) - Fen-Long Li; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Plant Systematics and Evolution, 2013)

Short Peptide Segment and Insulin Co-Assembly Forms Cytotoxic Oligomers - Jie Mao; Mei-Sha Chen; Yong-Xiang Chen; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2013)

Reduced expression of aquaporin 9 in tubal ectopic pregnancy - Yin Fen Ji; Li You Chen; Kai Hong Xu; Ji Fen Yao; Yi Fu Shi; Xue Jun Shanguan (Journal of Molecular Histology, 2013)

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings - Shin-Lon Ho; Li-Fen Huang; Chung-An Lu; Siou-Luan He; Chun-Chin Wang; Sheng-Ping Yu; Jychian Chen; Su-May Yu (Plant Molecular Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Biomechanical features of eccentric cambial growth and reaction wood formation in broadleaf tree branches - Ching-Chu Tsai; Li-Fen Hung; Ching-Te Chien; Shiang-Jiuun Chen; Yan-San Huang; Ling-Long Kuo-Huang (Trees, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Baseline human papillomavirus infection, high vaginal parity, and their interaction on cervical cancer risks after a follow-up of more than 10 years - Shu-Fen Liao; Wen-Chung Lee; Hui-Chi Chen; Li-Chung Chuang; Mei-Hung Pan; Chien-Jen Chen (Cancer Causes & Control, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Study of Lead Level During Pregnancy by Application of Synchrotron Radiation Micro XRF - Yongpeng Tong; Huibin Sun; Qi Luo; Jinxing Feng; Xiaohong Liu; Feng Liang; Fen Yan; Ke Yang; Xiaohan Yu; Yulan Li; Jianmin Chen (Biological Trace Element Research, 2011)

Performance of struvite precipitation during pretreatment of raw landfill leachate and its biological validation - Li Xiu-Fen; Dolores Barnes; Chen Jian (Environmental Chemistry Letters, 2011)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Human herpesvirus 8 viral FLICE-inhibitory protein retards cell proliferation via downregulation of Id2 and Id3 expression - Yi-Fen Wang; Lin-Yu Wang; Yi-Ling Li; Huey-Wen Shyu; Yee-Hsuan Chiou; Miao-Chen Chou; Kuan-Hua Lin; Ming-Hong Tai; Chang-Yu Chen (Molecular and Cellular Biochemistry, 2010)

Infliximab treatment in two Chinese patients with psoriatic arthritis - Xi Xie; Jin-wei Chen; Fen Li; Jing Tian; Jie-sheng Gao; David Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

The Association of Metallothionein-4 Gene Polymorphism and Renal Function in Long-Term Lead-Exposed Workers - Hsin-I Chen; Yu-Wen Chiu; Yu Kuei Hsu; Wan-Fen Li; Yi-Chun Chen; Hung-Yi Chuang (Biological Trace Element Research, 2010)

Bioturbation of Burrowing Crabs Promotes Sediment Turnover and Carbon and Nitrogen Movements in an Estuarine Salt Marsh - Jin Qing Wang; Xiao Dong Zhang; Li Fen Jiang; Mark D. Bertness; Chang Ming Fang; Jia Kuan Chen; Toshihiko Hara; Bo Li (Ecosystems, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Fast and Accurate Registration Techniques for Affine and Nonrigid Alignment of MR Brain Images - Jia-Xiu Liu; Yong-Sheng Chen; Li-Fen Chen (Annals of Biomedical Engineering, 2010)

Sensory Acquisition in the Cerebellum: An fMRI Study of Cerebrocerebellar Interaction During Visual Duration Discrimination - Lynn Y. L. Shih; Li-Fen Chen; Wen-Jui Kuo; Tzu-Chen Yeh; Yu-Te Wu; Ovid J. L. Tzeng; Jen-Chuen Hsieh (The Cerebellum, 2009)

Effects of saltmarsh invasion by Spartina alterniflora on arthropod community structure and diets - Yu-Tong Wu; Cheng-Huan Wang; Xiao-Dong Zhang; Bin Zhao; Li-Fen Jiang; Jia-Kuan Chen; Bo Li (Biological Invasions, 2009)

The dipeptidyl carboxypeptidase of Escherichia coli novablue: overproduction and molecular characterization of the recombinant enzyme - Hsiang-Ling Chen; Chen-Tien Chang; Long-Liu Lin; Tein-Yu Li; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2009)

A population-based, case–control study of green tea consumption and leukemia risk in southwestern Taiwan - Yau-Chang Kuo; Chu-Ling Yu; Chen-Yu Liu; Su-Fen Wang; Pi-Chen Pan; Ming-Tsang Wu; Chi-Kung Ho; Yu-Shing Lo; Yi Li; David C. Christiani (Cancer Causes & Control, 2009)

The Temporal and Spatial Variations of Acid Aerosols in the GeothermalArea of Metropolitan Taipei, Taiwan - I-Fang Mao; Li-Ting Chen; Yen-Neng Wang; Sheng-Fen Yang; Huei-Chen Chen; Mei-Lien Chen (Archives of Environmental Contamination and Toxicology, 2005)

Recognition of Motor Imagery Electroencephalography Using Independent Component Analysis and Machine Classifiers - Chih-I Hung; Po-Lei Lee; Yu-Te Wu; Li-Fen Chen; Tzu-Chen Yeh; Jen-Chuen Hsieh (Annals of Biomedical Engineering, 2005)

Chemical Modification of Insulin by N-phosphorylation - Yan Liu; Peng-xiang Xu; Jian-bo Hou; Li-feng Yang; Jin-an Chen; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2005)

Polyacetylenes Function as Anti-Angiogenic Agents - Li-Wha Wu; Yi-Ming Chiang; Hsiao-Ching Chuang; Sheng-Yang Wang; Ga-Wen Yang; Ya-Huey Chen; Ling-Ya Lai; Lie-Fen Shyur (Pharmaceutical Research, 2004)

The N-Terminal Signal Sequence and the Last 98 Amino Acids Are Not Essential for the Secretion of Bacillus sp. TS-23 α-Amylase in Escherichia coli - Huei-Fen Lo; Long-Liu Lin; Chien-Cheng Li; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2001)